Speaking Skills Distribution Through Storytelling in First Grade Students: Distribusi Keterampilan Berbicara Melalui Bercerita pada Siswa Kelas Satu - Friska Nur Fadilah (Academia Open, 2025)
General Background: Speaking competence is a fundamental component of language education in elementary schools and supports daily communication and classroom participation. Specific Background: First grade students often demonstrate varied oral abilities, and storytelling activities are commonly used to elicit verbal expression. Knowledge Gap: Empirical descriptions of speaking skill levels and their underlying factors among early primary learners in authentic classroom settings remain limited. Aims: This research aims to identify the speaking skill levels of first grade students using a storytelling method and to explore factors associated with weak performance. Results: Using a descriptive qualitative design with classroom observation and teacher interviews, students’ abilities were categorized into high (21.4%), moderate (42.9%), and low (35.7%). Higher performance was associated with confidence and frequent family communication, moderate performance with limited fluency and uncertainty in pronunciation, and lower performance with shyness, fear of public speaking, and minimal communicative practice at home. Novelty: The study provides a structured qualitative classification of early primary speaking abilities linked to home interaction patterns within a real classroom context. Implications: These findings highlight the importance of communicative environments and storytelling activities in diagnosing and supporting oral language development in early elementary education. Highlights: Three performance tiers were identified among learners with unequal proportions. Family interaction patterns were closely associated with verbal confidence. Classroom hesitation was linked to fear, shyness, and limited practice. Keywords: Speaking Skills; Storytelling Method; Primary Education; Oral Communication; Qualitative Analysis